Polypoidal Choroidal Vasculopathy on Swept-Source Optical Coherence Tomography Angiography with Variable Interscan Time Analysis - Rebhun, Carl B. (2017)
Purpose: To use a novel optical coherence tomography angiography (OCTA) algorithm termed variable interscan time analysis (VISTA) to evaluate relative blood flow speeds in polypoidal choroidal vasculopathy (PCV). Methods: Prospective cross-sectional study enrolling patients with confirmed diagnosis of PCV. OCTA of the retina and choroid was obtained with a prototype swept-source OCT system. The acquired OCT volumes were centered on the branching vascular network (BVN) and polyps as determined by indocyanine-green angiography (ICGA). The relative blood flow speeds were characterized on VISTAOCTA. Results: Seven eyes from seven patients were evaluated. Swept-source OCTA enabled detailed enface visualization of the BVN and polyps in six eyes. VISTA-OCTA revealed variable blood flow speeds in different PCV lesion components of the same eye, with faster flow in the periphery of polyps and slower flow in the center of each polyp, as well as relatively slow flow in BVN when compared with retinal vessels. BVNs demonstrated relatively faster blood flow speeds in the larger trunk vessels and relatively slower speeds in the smaller vessels. Conclusions: Swept-source OCTA identifies polyps in most, but not all, PCV lesions. This limitation that may be related to relatively slow blood flow within the polyp, which may be below the OCTA's sensitivity. VISTA-OCTA showed heterogeneous blood flow speeds within the polyps, which may indicate turbulent flow in the polyps.